Exploring the barriers and gateways to intersubjectivity in dementia care: A meta‐ethnography. Issue 13 (20th August 2020) - Hodge, Gary; Froggatt, Katherine; Limmer, Mark; Bingley, Amanda
Abstract: Background: Behaviours that challenge in dementia, often described and diagnosed as behavioural psychological symptoms of dementia, are experienced by 75% of people living with dementia in care homes or hospital environments, with 43% of nurses and care providers reporting these behaviours as moderately or severely distressing to them. During behaviours that challenge moments in dementia, there is the potential for an intersubjective relationship to take place between the people living with dementia and the nurse. Aims: This review explores and synthesises literature to consider the presence of intersubjectivity in people living with dementia. If the ability to be intersubjective remains present for people living with dementia, it will consider how its presence can be nurtured to offer a positive intersubjective communication between the person living with dementia and their carer/nurse. Methods: The review used meta‐ethnography methodology to develop concepts that help us to understand the implications of existing research on the presence of intersubjectivity in people living with dementia, and its relationship to those providing their care. Sixteen electronic databases (including MEDLINE/PubMed, Wiley Online Library and Sage publications) and grey literature such as Alzheimer's Society and Department of Health across journals dating from 2000–2020 were searched. Eight studies were selected and reviewed for quality and relevance for a meta‐ethnographic literature synthesis of intersubjectivity in dementia. Conclusion: The meta‐ethnography concluded that people living with dementia continue to have the capacity to be intersubjective on an emotional level. Nurses and other care providers need to acknowledge the presence of "personhood" and "personness" in people living with dementia to nurture positive intersubjective care relationships. The meta‐ethnography has also been reviewed for reporting clarity against the EQUATOR checklist in the form of the eMERGe guideline (France et al., 2019).